Gendered livelihoods: migrating men, left-behind women and household food security in India. Issue 10 (2nd October 2020) - Choithani, Chetan
Abstract: This paper assesses the food security implications of the out-migration of men for rural households headed by women. Recent transformations in the socio-economic landscape of the Global South involve an increasing number of rural households shifting towards urban-nonfarm, migration-based livelihoods. In many rural societies, social and cultural norms restricting women's mobility means migration is usually undertaken by men, leading to a phenomenon of left-behind women. The absence of men requires women to assume the role of household heads. This often triggers fundamental changes in intrahousehold gender power relations. However, little is known about the effects of these changes on household food security outcomes. Drawing on primary field research in western Bihar in India, this article attempts to highlight interconnections between migration, women left behind and household food security and, in doing so, makes two key contributions. First, with a focus on gender social roles, the paper shows that the two oft-cited impacts of migration of men—'improved autonomy' and 'increased responsibility' for left-behind women—provide conceptual pathways to understand migration-gender-food security linkages. Second, it provides evidence on how changes in women's roles under conditions of such migration intersect with household food security. The findings indicate a gender-based disadvantage in food security outcomes faced by household headed by women, offsetting even the potentially positive influence of improved female autonomy. The paper argues for the need to address socio-economic mechanisms underpinning gender-based vulnerabilities to food security.